Qian jia ming yang chang wei yin shi : da zi ban = Stomach - Qian, Jiaming, 1957- (Beijing: China Light Industry Press, 2022)
This book reveals the key points of diet for regulating the stomach from many aspects such as nutrients, eating habits, homemade ingredients, and Chinese medicinal materials for both medicine and food, and gives symptomatic dietary therapy and measures to strengthen gastrointestinal function for different gastrointestinal diseases, as well as gastrointestinal nourishment programs for different groups of people and different seasons.
Text in simplified Chinese scripts
Keywords: Gastroenterology -- Diseases -- Diet therapy -- Recipes; Cookbooks